2014
DOI: 10.1039/c3sm52614c
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive PNIPAAM bottlebrush polymers with tailored side-chain length and end-group structure

Abstract: We explore the phase behaviour, solution conformation, and interfacial properties of bottlebrush polymers with side-chains comprised of poly(N-isopropylacrylamide) (PNIPAAM), a thermally responsive polymer that exhibits a lower critical solution temperature (LCST) in water. PNIPAAM bottlebrush polymers with controlled side-chain length and side-chain end-group structure are prepared using a "grafting-through" technique. Due to reduced flexibility of bottlebrush polymer side-chains, side-chain end-groups have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 36 publications
2
100
0
Order By: Relevance
“…This implies that solubility and the side chain length play important roles in determining the conformation of bottlebrush polymers. 45 It is interesting to note that such nonmonotonic relation between the side chain length and the size of the bottlebrush polymer was also found from Figure 4 and 5 in ref 6, although the polymer is different. In CGMD with HSP potential, however, R g showed monotonic changes with increase side chain length.…”
Section: Resultsmentioning
confidence: 72%
“…This implies that solubility and the side chain length play important roles in determining the conformation of bottlebrush polymers. 45 It is interesting to note that such nonmonotonic relation between the side chain length and the size of the bottlebrush polymer was also found from Figure 4 and 5 in ref 6, although the polymer is different. In CGMD with HSP potential, however, R g showed monotonic changes with increase side chain length.…”
Section: Resultsmentioning
confidence: 72%
“…It should be noted that the reduction in interfacial tension by PNPs and star polymers is at most by one order of magnitude (from roughly 25 to 1 mN/m) . By comparison, surfactant additives can lead to much greater reductions in oil‐water interfacial tension, down to 0.001 mN/m 2 and below.…”
Section: Pnps For Mobility Controlmentioning
confidence: 99%
“…More recently, Saigal et al reported stable oil‐in‐water emulsions using silica nanoparticles coated with a pH responsive polymer, and they found that the most stable emulsions were formed at lower polymer chain grafting densities . Related studies on star polymers, bottlebrush polymers, and paramagnetic particles with adsorbed amphiphilic polymers found stable emulsions and reductions in the oil‐water interfacial tension at relatively low (0.1 wt %) particle contents . Alvarez et al evaluated the dynamic reduction in interfacial tension of air and water in the presence of PNPs while changing the grafting density of the polymer brushes and showed that the polymer coating is a key factor in reducing the interfacial tension of air and water using PNPs .…”
Section: Pnps For Mobility Controlmentioning
confidence: 99%
“…Due to steric effects, initiation and propagation can be challenging with less reactive polymerizable end‐groups such as methacrylates 31,32. As a result, ring‐opening metathesis polymerization (ROMP) of high strained cyclic olefins has successfully produced well‐defined bottlebrush polymers due to its wide functional group tolerance,33–37 fast polymerization rate, high MM conversion, high molecular weights (MW), and a narrow molecular weight distribution (MWD), typically, by using the fast initiating third‐generation Grubbs catalyst (G3) 38. Different polymerizable terminal norbornene or anchor groups of MMs influence the ROMP propagation rate due to steric and electronic effects 39–41.…”
Section: Introductionmentioning
confidence: 99%